The Geophytes of Sakarya City - Mehmet Sağıroğlu (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Sakarya city is within the Europe-Siberia phytogeographic region in Turkey. The effect of the Black Sea climate is usually seen in the study area. Black sea climate is effective in the northern part, while the Mediterranean climate is generally dominat in the South. In the area under the influence of the Mediterranean climate, there is a vegetation where the maquis-pseudomaquis communities are seen. The main research area of this study is chosen to be the geophyte plants collected in the city of Sakarya, Turkey. 1051 plant specimens were collected during field studies between 2009-2020. From the plant collection, 220 taxa and 80 genus belonging to 29 families have been identified. 18 of these taxa, are endemic. Of the total taxa in the area are 40 elements Euro-Sibirian, 41 widespread, 79 Mediterrenian, 7 Iranian-Turan, 16 Euxine, 34 phytogeographically unknown, 1 Hyrcano, 1 Hyrcano-Euxine, 1 North Americana elements.